2013
DOI: 10.1159/000354409
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Etiology of Congenital Hypothyroidism Detected through an Argentine Neonatal Screening Program (1997-2010)

Abstract: Introduction: We retrospectively assessed the incidence of congenital hypothyroidism (CH) detected through our neonatal screening program between 1997 and 2010. We describe the diagnostic characteristics of the detected population and verify the impact of a TSH cutoff (CO) change. Patients and Methods: Screening was based on TSH determination on dried blood spot on filter paper samples (IFMA) using a 15 mU/l blood CO until 12/2002 (P1) and 10 mU/l thereafter (P2). Patients were classified as having transient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
(37 reference statements)
2
24
0
5
Order By: Relevance
“…Two recent studies have characterized in more detail the factors contributing to the rising incidence of congenital hypothyroidism. In a study of the Argentine newborn screening program over 14 years (1997-2010), the incidence of congenital hypothyroidism increased by 31% (from 1 : 2619 to 1 : 1997), with 42% of the increment attributable directly to a decrease in the screening TSH cut-off from greater than 15 mIU/l to greater than 10 mIU/l [10]. Olivieri et al [11 && ] similarly analyzed data from the Italian network of regional newborn screening programs over a 22-year period (1987-2008) during which TSH cut-offs decreased from greater than 20 mIU/l to greater than 7-15 mIU/l.…”
Section: Incidence Of Congenital Hypothyroidismmentioning
confidence: 99%
“…Two recent studies have characterized in more detail the factors contributing to the rising incidence of congenital hypothyroidism. In a study of the Argentine newborn screening program over 14 years (1997-2010), the incidence of congenital hypothyroidism increased by 31% (from 1 : 2619 to 1 : 1997), with 42% of the increment attributable directly to a decrease in the screening TSH cut-off from greater than 15 mIU/l to greater than 10 mIU/l [10]. Olivieri et al [11 && ] similarly analyzed data from the Italian network of regional newborn screening programs over a 22-year period (1987-2008) during which TSH cut-offs decreased from greater than 20 mIU/l to greater than 7-15 mIU/l.…”
Section: Incidence Of Congenital Hypothyroidismmentioning
confidence: 99%
“…We used the terms 'congenital hypothyroidism and epidemiology' and this led, for the years 2009-2013, to the identification of six population-based studies that reported time trends, over periods of 10 years or more, in the prevalence of CH identified through neonatal screening [11][12][13][14][15][16]. These studies are summarized in TABLE 1: all reported an overall increase, although this increase varied from 1.4-to 1.8-fold.…”
Section: Abstract: Athyreosis • Birth Defects • Congenital Hypothyroimentioning
confidence: 99%
“…Both in the Québec and the Buenos Aires experience [12,16], lowering screening TSH cutoffs resulted in identifying cases of thyroid ectopy that would have been missed with higher cutoffs. Thyroid function in patients with thyroid ectopy tends to remain stable over time [42,43].…”
Section: Expert Commentarymentioning
confidence: 99%
“…At birth, most countries effectively screen for primary CH by thyrotropin (TSH) determination [1]. However, this approach misses central CH (CCH), which is caused by disorders of the hypothalamic-hypophyseal system and characterized by impaired TSH production, resulting in low circulating thyroid hormones in combination with low, inappropriately normal, or slightly elevated TSH levels [2].…”
Section: Introductionmentioning
confidence: 99%